Amniotomy shortens the induction delivery interval (Community Based Medical Journal, 2013)
Amniotomy or Artificial rupture of membrane is commonly performed procedure in obstetrics. It induces and or accelerates the progress of labour. It is done by artificial rupture of forebag of amniotic membrane. It causes local increase of prostaglandin which interact with collagenous framework and matrix of cervix, converting it from a rigid structure to a soft distensible organ. Release of amniotic fluid shortens muscle bundles of myometrium, strength and duration of contractions are thereby increased and more rapid contraction sequence follows. For this purpose amniotomy as a method of induction of labour may benefit in the way of reducing time interval and operative intervention. This study was conducted with the aim and objectives to evaluate cases in terms of indication, determine amnitomy delivery interval, analyze outcome of amniotomy in labour, find out cases needed for intervention during the process and detect any maternal and fetal complication that may arise as a result of amniotomy. This cross-sectional study was undertaken among 110 cases in Sir Sallimullah Medical College and Mitford Hospital over a period of one year from December1999 to December2000. Out of 110 patients 58 patients were multigravida and 52 were primigravida and their mean age was 25.3 years. Amniotomy was done in these patient with mean cervical dilatation of 3.9 cm. Amniotomy alone was done in 88 cases. Mean amniotomy-delivery interval was 4 hours 54 minutes and 90(81.8%) patients delivered normally; 89.1% babies were healthy. Amniotomy can not be used in remote areas of our country. Though it may shorten labour by augmentation and may contribute in reducing maternal morbidity and mortality but there is potential risk of cord prolapse, abruption placenta, risk of infection, so it can be done in institution with proper supervision. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16702 Community Based Medical Journal 2013 July: Vol.02 No 02: 67-70